IDENTIFICATION OF AUTHENTICITY BASED ON DIGITAL IMAGES USING LOCAL BINARY PATTERN AND SUPPORT VECTOR MACHINE METHODS - DIAN NIKITA SARI; Muhammad Ikhsan; Armansyah (Sean Institute, 2022)
Technological progress has an influence on development. Where the influence that arises can be in the form of positive or negative influences related to community behavior in utilizing and applying existing information technology. Paper money is a basic need in society where its use is as a means of payment, either cash or electronically. Counterfeit money is currency whose production is carried out without any legal approval from the state or government on the official website of Bank Indonesia. Counterfeit money in Indonesia from 2014 to 2018 has decreased and increased on a national scale. In this study the authors want to make a study to be able to distinguish counterfeit money or real money with the concept of Computer Science in the field of image processing using extraction and classification techniques. In this study, the extraction technique used is texture extraction with LBP and Classification using SVM to be able to recognize the authenticity of banknotes using the MATLAB application as a means to complete the analysis process